2019
DOI: 10.1002/dev.21865
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of autonomic function in the late term fetus: The effects of sex and state

Abstract: Researchers have reported associations between fetal sex and heart rate (FHR) and heart rate variability (FHRV) but rarely in the context of fetal behavioral sleep state. We examined differences in measures of fetal autonomic function by sex and sleep state. Fetal abdominal ECG monitoring technology was used to measure FHR and two measures of FHRV—standard deviation of FHR (SD) and beat‐to‐beat variability (RMSSD). FHR and movement patterns were also recorded with standard Doppler ultrasound monitor technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
7
1
Order By: Relevance
“…But these differences were not reflected in the respective latency values. While there have been recent reports (DiPietro & Voegtline, 2017;Wheelock et al, 2019;Zavala, Ecklund-Flores, Myers, & Fifer, 2019) showing differences in fetal heart rate variability and functional connectivity in the brain between male and female fetuses, our results of the effect of GA period, fetal sex, and their interaction-based testing of first-peak latencies for AER and VER for fetal-sex differences were not significant. Again this needs to be examined further, and as mentioned above, since latency trajectory may be different for each of the high-risk conditions, by combining them in one group we may have obliterated the potential effects of GA and sex.…”
Section: Discussioncontrasting
confidence: 99%
“…But these differences were not reflected in the respective latency values. While there have been recent reports (DiPietro & Voegtline, 2017;Wheelock et al, 2019;Zavala, Ecklund-Flores, Myers, & Fifer, 2019) showing differences in fetal heart rate variability and functional connectivity in the brain between male and female fetuses, our results of the effect of GA period, fetal sex, and their interaction-based testing of first-peak latencies for AER and VER for fetal-sex differences were not significant. Again this needs to be examined further, and as mentioned above, since latency trajectory may be different for each of the high-risk conditions, by combining them in one group we may have obliterated the potential effects of GA and sex.…”
Section: Discussioncontrasting
confidence: 99%
“…An increase in RMSSD was also found. Nevertheless, proportionally SDNN increased more than RMSSD during fetal activity (Brändle et al, 2015 ; Stone et al, 2017 ; Zavala et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Wheeler et al showed a significant association between active fetuses and SDNN with a higher SDNN in active fetuses compared to resting fetuses in term pregnancies (Wheeler et al, 1980). This was confirmed by Frank et al (2006), Brändle et al (2015) Stone et al (2017, and Zavala et al (2019). An increase in RMSSD was also found.…”
Section: Time Domain Parameters and Fetal Body Movementsmentioning
confidence: 89%
“…Specifically, the post-dose decrease in STV was observed among SRI-Depressed group male fetuses, compared with the relative stability in STV between assessments in SRI-Depressed females. Indeed, sex difference in fetal HR variability have been reported in lowrisk singleton pregnancies (98,99), for example in a large CTG study, males had lower baseline HR but higher STV than females throughout gestation (78). Although basal HR and STV in males and females in the Control group did not differ significantly, SRI-Depressed males did have higher STV than SRI-Depressed females at the baseline/pre-dose assessment, pointing to a chronic/sustained SRI-related sex difference that is evident when maternal depressive symptoms persist.…”
Section: Acute Sri Effects On Fetal Hr Variability Are Sex-specificmentioning
confidence: 99%